Antigen Ekskretori-Sekretori Cacing Jantung (Dirofilaria immitis) Jantan dan Betina yang Berpotensi Sebagai Marka Diagnosis (EXCRETORY-SECRETORY ANTIGENS OF MALE AND FEMALE HEART WORMS (DIROFILARIA IMMITIS) WHICH POTENTIALLY AS A DIAGNOSTIC MARKER) - Erawan, I Gusti Made Krisna; Tjahajati, Ida; Nurcahyo, Wisnu; Asmara, Widya (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Heart worm (Dirofilaria immitis) is the causative agent of a serious parasitic disease in dogs.Dirofilariasis is generally diagnosed by microfilariae examination and specific antigen testing. Microfilariaeexamination has low sensitivity due to occult infections. The available antigen test at this time is able todetect circulating antigens secreted by adult female worms only. The aim of the present study was toidentify male (MES) and female (FES) heart worms excretory-secretory antigens which have the potentialas a diagnostic targets. Identification of antigen was done by sodium dodecyl sulphate polyacrylamide gelelectrophoresis (SDS-PAGE) and Western Blotting analysis. The results of this study indicated that therewere differences between the MES and the FES profiles. The results showed 12 bands in MES (14–118kDa) and 18 bands in FES (10–205 kDa). Protein with a molecular weight of 59 kDa has the potential asdiagnostic markers of dirofilariasis.
Keywords: excretory-secretory antigens, Dirofilaria immitis, diagnostic marker, SDS-PAGE, Western Blotting